Trypanosoma cruzi seroprevalence and associated factors in women in Casanare–Colombia - Díaz, Angela Liliana Monroy (J Parasit Dis, 2020)
Chagas disease is caused by the parasite Trypanosoma cruzi and transmitted mainly by triatomines and from mothers to children. In Colombia, this disease is a public health problem and due to its high endemicity and vertical transmission, women are susceptible populations that must be evaluated. Our objective was to determinate the Trypanosoma cruzi seroprevalence and factors associated with women in Pore (Municipality), Casanare, Colombia. Cross-sectional study. A sample of 230 healthy volunteer women, 15 years or older, without previous diagnosis of Chagas disease was taken; the serological analysis was done using the Chagas ELISA IgG and IgM and indirect Hemagglutination (HAI) technique. In addition, a survey was applied to each participant in order to explore the presence of factors that could be associated with a positive test result. The seropostitivity found in Pore Casanare’s women was 16.9% (39/230, 95% CI 12.1–21.7), additionally it was found that rural origin, the coexistence with animals, especially chickens, age, low level schooling and housing material are factors associated with T. cruzi infection in this population. The results of this study indicate the importance of conducting extensive seroepidemiological studies in populations of endemic areas, due to the difficulty in detecting cases in the acute phase; therefore, screening allows the establishment of a follow-up and treatment time line that contributes to the interruption of the transmission vertical.